KRAS mutations promote the intratumoral colonization of enterotoxigenic bacteroides fragilis in colorectal cancer through the regulation of the miRNA3655/SURF6/IRF7/IFNβ axis - Yizhen Chen; Shaolin Liu; Song Tan; Yuanyuan Zheng; Yifan Chen; Changshun Yang; Shengtao Lin; Yulong Mi; Weihua Li (Gut Microbes)
KRAS mutations are associated with poor prognosis in colorectal cancer (CRC). Although the association between the gut microbiota and CRC has been extensively documented, it is unclear whether KRAS mutations can regulate the gut microbiota. Metagenomics has identified changes in the diversity of the gut microbiota in CRC due to KRAS mutations. Specifically, KRAS mutations positively correlate with the abundance of the bacteroides. Understanding how to regulate the classic carcinogenic bacterium within the bacteroides, such as enterotoxigenic bacteroides fragilis (ETBF), to enhance treatment efficacy of tumors is a key focus of research. Mechanistically, we found that the reduction of miR3655 is indispensable for KRAS mutation-promoted proliferation of CRC and the abundance of ETBF. miR3655 targets SURF6 to inhibit its transcription. Further transcriptomic sequencing revealed that SURF6 promotes intratumoral colonization of ETBF in CRC by inhibiting the nuclear translocation and transcription levels of the IRF7, affecting the activation of the IFNβ promoter. Regulating miR3655 and SURF6 can promote IFNβ secretion in CRC, directly killing ETBF. These data indicate that KRAS mutations affect the intratumoral colonization of ETBF in CRC through the miR3655/SURF6/IRF7/IFNβ axis. This provides new potential strategies for treating CRC associated with KRAS mutations or high levels of ETBF.